The Long Way Toward Cooperation - Thomas Foth; Karen Block; Maren Stamer; Norbert Schmacke (Global Qualitative Nursing Research, 2015)
To better understand why cooperation between health care professionals is still often problematic, we carried out 25 semistructured face-to-face expert interviews with physicians and nurses in different rural and urban areas in northern Germany. Using Mayring’s qualitative content analysis method to analyze the data collected, we found that doctors and nurses interpreted interprofessional conflicts differently. Nursing seems to be caught in a paradoxical situation: An increasing emphasis is placed on achieving interprofessional cooperation but the core areas of nursing practice are subject to increasing rationalization in the current climate of health care marketization. The subsequent and systematic devaluation of nursing work makes it difficult for physicians to acknowledge nurses’ expertise. We suggest that to ameliorate interprofessional cooperation, nursing must insist on its own logic of action thereby promoting its professionalization; interprofessional cooperation cannot take place until nursing work is valued by all members of the health care system.